PENINGKATAN HASIL DAN KEAKTIFAN SISWA KELAS VI MATERI PLANET DALAM TATA SURYA MELALUI PARTNER CARD - Ahmad Safii (Universitas Muria Kudus, 2020)
The purpose of this study was to improve the results and activeness of learning natural science of planetary material in the solar system in Grade VI students of SDN Candi, Todanan District, Blora Regency. This study uses a partner card learning model by inviting students to understand concepts through paired card games. The methods used in partner cards include: discussion, discovery, and question and answer by training students to be active and creative in learning. Before using the model student learning outcomes were very low, from 20 students showing that there were as many as 3 students (15%) and as many as 17 students (85%) unfinished, causing an average student grade of 39.5. In early learning, many students are lazy in learning and students tend to not be active in every activity. Many students forget the material that has been taught, both easy and difficult. In addition students also did not look active in group discussions and only a few students who seemed active. Based on student learning outcomes in the first learning cycle where the partner card game model has been known as many as 15 students or 75% have been completed and 5 students or 25% have not been completed. In the second cycle there was an increase in the number of students who had finished up by 18 students or 90% and only 2 students or 10% had not yet completed. The activeness of students in the first cycle also increased, with an average score of 3.2 in the good category and again in the second cycle of 3.6 in the excellent category.